The Relationship Between Informal Economy and Income Inequality: An Econometric Analysis for BRICS Countries - Kum, Hakan (International Journal of Economics and Financial Issues, 2024)
This research investigates the intricate relationship between the informal economy and income inequality in BRICS nations from 2000 to 2018. Defining the informal economy as economic activities outside the formal sector contributing to GDP, the study addresses a gap in existing literature that tends to overlook this sector’s impact on income distribution. Utilizing panel unit root and panel cointegration tests, the findings reveal a significant and direct correlation between income inequality, the informal economy, and GDP in BRICS countries. The study uncovers a noteworthy revelation: a 1% increase in the informal economy leads to a substantial 3.24% rise in the GINI coefficient, showcasing the informal sector’s profound influence on income inequality. Country-specific analyses identify India and Russia as frontrunners in this correlation, with China, Brazil, and South Africa following suit. Intriguingly, the analysis indicates that while a 1% rise in official GDP slightly worsens income distribution, the informal economy exerts a disproportionately negative impact on income inequality. This research provides valuable insights for policymakers, emphasizing the need to consider the informal economy’s role in crafting effective strategies for mitigating income inequality within the BRICS context.